Abu Bakar and modern Johor: The question of modernisation and westernisation in Malay tradition - A Rahman Tang Abdullah (Faculty of Arts and Social Sciences, UM, 2008)
This article discusses the application of modernisation in the process of transformation of Johor during Abu Bakar's reign from 1862 to 1895. The transformation here refers to the transition from a traditional to modern circumstances in Malay society. The aim of the article is to evaluate and construct a distinction between 'modernisation' and 'westernisation' from a terminological perspective. The discussion leads to the conclusion that the process of transformation in Johor should be regarded as 'modernisation and not westernisation' simply because the process of transformation is seen as complemtary to the Malay tradition. The hypothesis is based on the transformation in governmental affairs and the Johor's constitution of 1895.